(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Kolhapur District, situated in the south western part of Maharashtra, is renowned for its rich agricultural heritage and thriving local economy. The district’s climate, coupled with its agricultural practices, creates a unique setting for poultry farming. Kolhapur’s contribution to egg production is influenced by factors such as feed availability, veterinary care, market access, and local management practices. This study aims to explore the dynamics of egg production in Kolhapur District with in the broader context of Maharashtra. Through this focused analysis, the study will contribute valuable knowledge to stake holders, including policy makers, farmers, and industry experts, fostering informed decision-making and promoting the advancement of egg production practices in Kolhapur and Maharashtra at large.